Protective role of melatonin in cardiac ischemia‐reperfusion injury: From pathogenesis to targeted therapy. Issue 3 (8th February 2018) - Zhou, Hao; Ma, Qiang; Zhu, Pingjun; Ren, Jun; Reiter, Russel J.; Chen, Yundai
Abstract: Acute myocardial infarction (MI) is a major cause of mortality and disability worldwide. In patients with MI, the treatment option for reducing acute myocardial ischemic injury and limiting MI size is timely and effective myocardial reperfusion using either thombolytic therapy or primary percutaneous coronary intervention (PCI). However, the procedure of reperfusion itself induces cardiomyocyte death, known as myocardial reperfusion injury, for which there is still no effective therapy. Recent evidence has depicted a promising role of melatonin, which possesses powerful antioxidative and anti‐inflammatory properties, in the prevention of ischemia‐reperfusion (IR) injury and the protection against cardiomyocyte death. A number of reports explored the mechanism of action behind melatonin‐induced beneficial effects against myocardial IR injury. In this review, we summarize the research progress related to IR injury and discuss the unique actions of melatonin as a protective agent. Furthermore, the possible mechanisms responsible for the myocardial benefits of melatonin against reperfusion injury are listed with the prospect of the use of melatonin in clinical application.